2003
DOI: 10.1007/s00299-003-0619-4
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the B subunit of Escherichia coli heat-labile enterotoxin as a fusion protein in transgenic tomato

Abstract: Epitopes often require co-delivery with an adjuvant or targeting protein to enable recognition by the immune system. This paper reports the ability of transgenic tomato plants to express a fusion protein consisting of the B subunit of the Escherichia coli heat-labile enterotoxin (LTB) and an immunocontraceptive epitope. The fusion protein was found to assemble into pentamers, as evidenced by its ability to bind to gangliosides, and had an average expression level of 37.8 microg g(-1) in freeze-dried transgenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(50 citation statements)
references
References 32 publications
0
47
0
3
Order By: Relevance
“…Based on the results of the In other study, we found that the amount of LTB protein of in vitro transgenic tomato leaves was approximately 0.8-1.0% of TSPs (Nhi et al 2010). Walmsley et al (2003) found that the LTB protein of transgenic tomato fruit was assembled into pentamers. It showed an average expression level of 37.8 μg/g in freeze-dried transgenic tissues.…”
Section: Detection Of Transgene In Transformed Plantsmentioning
confidence: 99%
“…Based on the results of the In other study, we found that the amount of LTB protein of in vitro transgenic tomato leaves was approximately 0.8-1.0% of TSPs (Nhi et al 2010). Walmsley et al (2003) found that the LTB protein of transgenic tomato fruit was assembled into pentamers. It showed an average expression level of 37.8 μg/g in freeze-dried transgenic tissues.…”
Section: Detection Of Transgene In Transformed Plantsmentioning
confidence: 99%
“…Varying lengths of proteins have been fused to LT-B and CT-B with or without a hinge and expressed in both bacteria and plant systems (Lipscombe et al, 1991, Smerdou et al, 1996, Luci et al, 2006, Walmsley et al, 2003. However, success of the fusion protein approach has to be evaluated on a case-by-case basis (Rigano et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies were carried out involving expression of LT-B and CT-B fusions with unrelated antigens in plants (Kim et al, 2004a, Kim et al 2004b, Kim et al, 2004c, Kang et al, 2006, Walmsley et al, 2003 The present work aimed at utilizing LT-B and CT-B as carriers for a human protein 'amyloid beta' and its epitopes to generate an orally administered plant-derived vaccine against Alzheimer's disease (AD). Alzheimer's disease is a neurodegenerative disorder characterized by cognitive decline, memory loss, language deficits and personality changes.…”
Section: 7mentioning
confidence: 99%
See 1 more Smart Citation
“…Algunos ejemplos en la literatura demuestran el gran potencial biotecnológico de los frutos transgénicos para la mejora de caracteres agronómicos (Carmi et al, 2003;Ficcadenti et al, 1999), valor nutricional (Mehta et al, 2002;Muir et al, 2001), rasgos organolépticos (Davidovich-Rikanati et al, 2007), e incluso valor terapéutico (Jani et al, 2002;Ma et al, 2003;Ramirez et al, 2007;Walmsley et al, 2003). A pesar de estos casos, las herramientas disponibles para la modificación genética resultan ser bastante rudimentarias, basándose en la mayoría de los casos en unos pocos promotores de fruto bien caracterizados.…”
Section: Promotores De Tomate Utilizados En Biotecnologíaunclassified